Cancer incidence and mortality in the Swedish polyurethane foam manufacturing industry. - Hagmar, L (1993)
Toluene diisocyanate (TDI) and methylene diphenyldiisocyanate (MDI) are used in large quantities in the polyurethane foam manufacturing industry. Both substances are mutagenic and at least TDI is carcinogenic to animals, but the occupational hazard with respect to cancer is not known. Cancer incidence and mortality patterns were therefore investigated in a cohort of 4154 workers from nine Swedish plants manufacturing polyurethane foam, employed for at least one year. Each workplace and job task in the nine plants was categorically assessed for each calendar year by an experienced occupational hygienist, for "no exposure", "low or intermittent exposure", or "apparent exposure" to TDI and MDI. The observed deficit for all cause mortality (standardised mortality ratio (SMR) 0.78, (95% confidence interval (95% CI) 0.66-0.93) became smaller (SMR 0.92) excluding the first 10 years since the start of exposure and was ascribed to a healthy worker effect. No increased risk for death from bronchial obstructive diseases was found. An almost statistically significant deficit occurred for all malignant neoplasms (standardised incidence ratio (SIR) 0.81, 95% CI 0.63-1.02); slight (not significant) increased risks were found for rectal cancer (SIR 1.66) and non-Hodgkin's lymphoma (SIR 1.53). The SIR for non-Hodgkin's lymphoma increased to 2.80 (95% CI 0.76-7.16) when the first 10 years since first exposure were excluded from the observation period. The corresponding figure for rectal cancer was 1.92 (95% CI 0.52-4.92). Further restricting the analysis to those who had experienced an apparent exposure to TDI or MDI increased the SIR for both rectal cancer (3.19, 95% CI 0.66-9.33), and non-Hodgkin's lymphoma (3.03, 95% CI 0.37-10.9). These estimates were based, however, on few incident cases. As the cohort is still young and little time has elapsed since the start of exposure, future follow ups will enable a more conclusive evaluation.